Human placental hematopoietic stem cell derived natural killer cells (CYNK-001) mediate protection against influenza a viral infection. Issue 5 (30th November 2022) - Gleason, Joseph; Zhao, Yuechao; Raitman, Irene; Kang, Lin; He, Shuyang; Hariri, Robert
ABSTRACT: Influenza A virus (IAV) infections are associated with a high healthcare burden around the world and there is an urgent need to develop more effective therapies. Natural killer (NK) cells have been shown to play a pivotal role in reducing IAV-induced pulmonary infections in preclinical models; however, little is known about the therapeutic potential of adoptively transferred NK cells for IAV infections. Here, we investigated the effects of CYNK-001, human placental hematopoietic stem cell derived NK cells that exhibited strong cytolytic activity against a range of malignant cells and expressed high levels of activating receptors, against IAV infections. In a severe IAV-induced acute lung injury model, mice treated with CYNK-001 showed a milder body weight loss and clinical symptoms, which led to a delayed onset of mortality, thus demonstrating their antiviral protection in vivo . Analysis of bronchoalveolar lavage fluid (BALF) revealed that CYNK-001 reduced proinflammatory cytokines and chemokines highlighting CYNK-001's anti-inflammatory actions in viral induced-lung injury. Furthermore, CYNK-001-treated mice had altered immune responses to IAV with reduced number of neutrophils in BALF yet increased number of CD8+ T cells in the BALF and lung compared to vehicle-treated mice. Our results demonstrate that CYNK-001 displays protective functions against IAV via its anti-inflammatory and immunomodulating activities, which leads to alleviation of disease burden and progression in a severe IAV-infected mice model. The potential of adoptive NK therapy for IAV infections warrants clinical investigation.